2010
DOI: 10.1007/s12149-010-0378-6
|View full text |Cite
|
Sign up to set email alerts
|

Is the predicted postoperative FEV1 estimated by planar lung perfusion scintigraphy accurate in patients undergoing pulmonary resection? Comparison of two processing methods

Abstract: PpoFEV1 values predicted by both the zone and LMMs overestimated the actual measured lung volumes in patients undergoing pulmonary resection in the early postoperative period. LMM is not superior to ZM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Prediction of postoperative lung function in patients undergoing pulmonary resection is an important factor that may determine the feasibility of the surgery. There have been reports of the usefulness of lung perfusion scintigraphy in predicting postoperative lung function (14,18,19). Tom Holvoet et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Prediction of postoperative lung function in patients undergoing pulmonary resection is an important factor that may determine the feasibility of the surgery. There have been reports of the usefulness of lung perfusion scintigraphy in predicting postoperative lung function (14,18,19). Tom Holvoet et al.…”
Section: Discussionmentioning
confidence: 99%
“…The segment method assumes 19 segments of both lungs and calculates the relative function of the segment preserved postoperatively (4). The conventional zone method divides the lung into upper, middle, and lower lung zones and then predicts postoperative lung function using each fraction of the total lung geometric mean counts (19). These segment and conventional zone methods could not fully reflect the structure of the lung and a method of manually drawing the ROI of each lobe like the lobar mapping method has been introduced (19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, divergent opinions on this issue can be met in the literature. Caglar et al [19] have shown that a thorough delineation of lung lobes in planar lung perfusion scintigrams does not improve accuracy of predicted postoperative FEV1 values as compared with a schematic division of lungs into lobes. Next, several authors applying both planar and SPECT methods did not observe any advantage of the latter in prediction of postoperative residual lung function [11,12,20].…”
Section: Discussionmentioning
confidence: 99%